Helping the Poor : the IMF's New Facilities for Structural Adjustment - Landell-Mills, Joslin (Washington, D.C. : International Monetary Fund, 1998)
Helping the Poor: the IMF's New Facilities for Structural Adjustment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet